2011
DOI: 10.4028/www.scientific.net/amr.189-193.4434
|View full text |Cite
|
Sign up to set email alerts
|

Reliability Analysis for Structure System with the Local Dented Plate

Abstract: In this paper, the influence of the local dented plate on ultimate strength is analyzed, and reliability calculation and sensitivity analysis expressions of the plate element with local dents are also proposed. For the structure system consisting of local dented plate elements, reliability analysis is developed, the calculation method of the global reliability index and sensitivity expressions of the reliability index are proposed. Finally, taking a numerical example of a cabin section of ship structure compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Hai et al [5] studied the influence of multiple defects namely initial distortions, weld residual stresses, cracks and local dents on ultimate strength of the plate and also derived expressions for reliability index and sensitivity analysis of the plate. Hai et al [6] in their work, proposed a method to determine global reliability index and sensitivity expression of reliability index of the plate structure with a local dent based on ultimate strength reduction factor. Raviprakash et al [7] in their work, numerically studied about the effect of transverse/longitudinal dent on the ultimate strength of a thin square plate under uni-axial compression and it was concluded that transverse dent affect the ultimate strength more drastically than the longitudinal dent.…”
Section: Introductionmentioning
confidence: 99%
“…Hai et al [5] studied the influence of multiple defects namely initial distortions, weld residual stresses, cracks and local dents on ultimate strength of the plate and also derived expressions for reliability index and sensitivity analysis of the plate. Hai et al [6] in their work, proposed a method to determine global reliability index and sensitivity expression of reliability index of the plate structure with a local dent based on ultimate strength reduction factor. Raviprakash et al [7] in their work, numerically studied about the effect of transverse/longitudinal dent on the ultimate strength of a thin square plate under uni-axial compression and it was concluded that transverse dent affect the ultimate strength more drastically than the longitudinal dent.…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1970 s TAGUCHI proposed the three design method to reduce the influence of uncertain factors on the quality, reliability design has been applied in many fields [1] [2]. Due to the random factors such as material properties, geometrical characteristic of structural member, load history and environmental condition, the fatigue life of structure often deviates from the design life of the airborne air conditioner.…”
Section: Introductionmentioning
confidence: 99%